Understanding and assessing child sexual maltreatment - Faller, Kathleen Coulborn; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2003)
This book provides practical information for students and professionals, complete with useful case studies. This second edition updates the techniques of assessment and includes more coverage of interventions following on from assessment.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Sexually abused children -- United States; Electronic books